V. KATAEV AS A HUMORIST AND SATIRIST - Likhodzievsky, Anatoliy; Yue, Zhao (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article presents the work of the famous Russian writer Valentin Kataev, who significantly contributed to the development of the satirical short novel genre in Russian literature in the first half of the XX century. The two most significant works of Kataev in this genre are analyzed — "Ehrendorf Island" and "Lord of Iron". The primary attention is paid to the specific problems of works, their figurative system, and targets of satirical criticism. The features of V. Kataev's satirical technique and methods of creating comic images and situations are studied. The article uses the method of typological comparison from the point of view of the satirical short novel genre and its interaction with other literary genres. The study provides relevant conclusions on the fruitful fusion of satire with the adventure novel and science fiction genres.
Keywords: satire; grotesque; satirical story; denunciation; adventure; comedy; philosophical ideas; author's position; action dynamics; fantasy